PENGARUH PENDIDIKAN KEWIRAUSAHAAN, SELF EFFICACY, LOCUS OF CONTROL DAN KARAKTER WIRAUSAHA PADA MINAT BERWIRAUSAHA (STUDY KASUS MAHASISWA EKONOMI & BISNIS UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ) - APRILDA YANTI (JURNAL ILMIAH SIMANTEK, 2020)
Many young people become unemployed, so that growing the spirit of entrepreneurship is believed to be an alternative toovercome the limitations of employment and reduce the number of unemployed. The purpose of this study is to analyze theeffect of entrepreneurship education, self efficacy, locus of control and entrepreneurial characteristics on interest in S1student entrepreneurship. The location of this study was at the Muhammadiyah University of North Sumatra, Faculty ofManagement. The sample used was 125 people. The study uses Random Sampling techniques and data collection withquestionnaires. The data analysis technique used is the classic assumption test, multiple linear regression, t-test, f-test anddeterminant coefficient. Based on the partial test (t test) it is known that there is a positive but not significant effect onentrepreneurship education on the interest in entrepreneurship. This is indicated by t count of 0.512 and sig of 0.610 wheresig> 0.05, there is a positive and significant effect of self efficacy on the interest in entrepreneurship. This is indicated by tcount of 7.167 and sig of 0.000 where sig <0.05, there is a positive but not significant effect of Locus of Control on theinterest in entrepreneurship. This is indicated by t arithmetic of 1.607 and sig of 0.111 where sig> 0.05, There is a positiveand significant influence of entrepreneurial character on the interest in entrepreneurship. This is indicated by t count of 4.794sig of 0.000 where sig <0.05. Based on the results of testing simultaneously there is a positive and significant effect ofentrepreneurship education, self efficacy, Locus of Control and entrepreneurial character on the interest in entrepreneurship.The F test results obtained F count value of 81.531 and sig of 0.000, where sig F <0.05. The coefficient of determination (R2)is 0.731.